Applicability of Pay-What-You-Want to High-Value Goods – A Case Study - Agnes Sophie Roggentin (Marketing Review St.Gallen, 2019)
This case study investigates the feasibility of Pay-What-You-Want pricing for goods of high monetary value. The author assumed that allocating a portion of the offered price to charity would mitigate customers' incentive to bargain. Yet, results show that customers pay prices too low to compensate for either the seller's input or a charitable cause.
Keywords: 650